2011
DOI: 10.1371/journal.pbio.1001131
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Sex-Specific Traits through Changes in HOX-Dependent doublesex Expression

Abstract: Analysis in Drosophila suggests that evolutionary changes in the spatial regulation of the transcription factor doublesex play a key role in the origin, diversification, and loss of sex-specific structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
195
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(212 citation statements)
references
References 63 publications
(90 reference statements)
13
195
1
3
Order By: Relevance
“…melanogaster shows noticeable sexual dimorphism in their SCR expression pattern as reported by the earlier studies (Barmina and Kopp, 2007;Tanaka et al, 2011) and the same pattern is observed in D. rajasekari in the present study. The prothoracic SCR expression domain in males extends upto the distal border of the ts1 whereas in case of female foreleg pupal disc, the expression will not extend to the distal margin.…”
Section: Marked Enhancement In Expression Of Scr Features the Speciessupporting
confidence: 92%
See 2 more Smart Citations
“…melanogaster shows noticeable sexual dimorphism in their SCR expression pattern as reported by the earlier studies (Barmina and Kopp, 2007;Tanaka et al, 2011) and the same pattern is observed in D. rajasekari in the present study. The prothoracic SCR expression domain in males extends upto the distal border of the ts1 whereas in case of female foreleg pupal disc, the expression will not extend to the distal margin.…”
Section: Marked Enhancement In Expression Of Scr Features the Speciessupporting
confidence: 92%
“…double sex, the somatic sex regulator gene is responsible for providing the sex specific information for the development of sex comb in D. melanogaster and other species of the cluster (Barmina and Kopp, 2007;Randsholt and Santamaria 2008;Tanaka et al, 2011). It is interesting that, dsx expression is also seen in the leg discs of species like D. willistoni and D. hydei, which do not have sexually dimorphic bristles on their tarsal segments, and in various other species like D. immigrans and Zaprionus tuberculatus, which do not have a sex comb but have certain other sexually dimorphic tarsal structures (Tanaka et al, 2011). In this context, it is possible that, changes in DAC protein, and gain in the expression level of SCR in the tarsal segments are earlier steps in the evolutionary switching over of the developmental program, and this might have been followed by establishing a link with the dsx pathway at a subsequent stage, culminating in the evolution of the sexually dimorphic new trait sex comb.…”
Section: Bric-a-brac Expression Is Not Altered During Sex Comb Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, recent studies have also revealed that dsx is a nexus for the evolution of sexually dimorphic traits; all cases understood at the molecular level involve either changes in cis-regulatory sequences of dsx target genes (11,12) or changes in the expression of dsx itself (13,14). In addition, the recent finding that developing Drosophila are mosaic for dsx expression-and thus are mosaic for the potential for sexual differentiation-has led to increased appreciation for the potential of evolution through tissuespecific changes in dsx activity (15).…”
mentioning
confidence: 99%
“…In addition, the recent finding that developing Drosophila are mosaic for dsx expression-and thus are mosaic for the potential for sexual differentiation-has led to increased appreciation for the potential of evolution through tissuespecific changes in dsx activity (15). Indeed, it was recently found that the diversification of sex combs in Drosophila species is correlated with changes in dsx expression patterns (14).…”
mentioning
confidence: 99%